Incomplete surgical excision of keratinocyte skin cancers: a systematic review and meta‐analysis. (1st June 2021) - Nolan, G.S.; Kiely, A.L.; Totty, J.P.; Wormald, J.C.R.; Wade, R.G.; Arbyn, M.; Jain, A.
Summary: Background: Keratinocyte or nonmelanoma skin cancer (NMSC) is the commonest malignancy worldwide. The usual treatment is surgical excision. Current guidelines underestimate incomplete excision rates. Objectives: We aimed to determine the risk of incomplete excision of NMSCs through a systematic review and meta‐analysis of primary clinical studies. Methods: A PRISMA‐compliant systematic review and meta‐analysis was performed using methodology proposed by Cochrane (PROSPERO CRD42019157936). A comprehensive search strategy was applied to MEDLINE, Embase, Scopus, CINAHL, EMCare, Cochrane Library and the grey literature (January 2000–27 November 2019). All studies were included except those on Mohs micrographic surgery, frozen section or biopsies. Abstract screening and data extraction were performed in duplicate. Risk of bias was assessed using a tool for prevalence/incidence studies. The primary outcome was the proportion of incomplete surgical excisions. A random‐effects model for pooling of binomial data was used. Differences between proportions were assessed by subgroup meta‐analysis and meta‐regression, which were presented as risk ratios (RRs). Results: Searching identified 3477 records, with 110 studies included, comprising 53 796 patients with 106 832 basal cell carcinomas (BCCs) and 21 569 squamous cell carcinomas (SCCs). The proportion of incomplete excisions for BCC was 11·0% [95% confidence interval (CI) 9·7–12·4] and for SCC 9·4% (95% CI 7·6–11·4). Proportions of incomplete excisions by specialty were: dermatology, BCCs 6·2% and SCCs 4·7%; plastic surgery, BCCs 9·4% and SCCs 8·2%; general practitioners, BCCs 20·4% and SCCs 18·9%. The risk of incomplete excision for general practitioners was four times that of dermatologists for both BCCs (RR 3·9, 95% CI 2·0–7·3) and SCCs (RR 4·8, 95% CI 1·0–22·8). Studies were heterogeneous ( I 2 = 98%) and at high risk of bias. Conclusions: The proportion of incomplete excisions is higher than previously reported. Excisions performed by specialists may lower the risk of incomplete excision.